Musical traces of hindustani culture in Malay ghazal - Meddegoda, Chinthaka Prageeth (2015)
Malay ghazal is a music genre developed in the twentieth century as entertainment music among the noble community that lived in Riau Lingga, Singapore and Johor. Matusky and Tan (2004) infer two theories explaining that Malay ghazal originated through Hindustani ghazal practices. Apparently, Malay ghazal practices in Malaysia include Hindustani musical instruments, i.e. tabla and harmonium as prominent musical instruments which are said to be brought by Indians who came to the Malay world for various purposes. In addition to harmonium and tabla, a typical Malay ghazal ensemble consists of music instruments such as gambus,violin, maracas, and marwas that accompany vocal renderings. However, today, Malay ghazal practices do not demonstrate obvious Hindustani music elements. Only the adaptation of Hindustani harmonium and tabla imply Hindustani musical appearances and sound to a certain extent. Even though Indian sources are undoubtedly mentioned in current literature, the degree of integrating Hindustani musical elements into Malay ghazal practices as well as social and ethnic relations to the music content is yet to be discussed. This study attempts to elucidate origin and evolution of Malay ghazal addressing questions regarding musical content and its relation to the Malay culture. The core questions are ‘what is known to Malaysian scholars and musicians on Hindustani cultural and musical elements in Malay ghazal, to what extent Hindustani musical elements are used in Malay ghazal, and which cross-cultural approaches in assimilating Malay ghazal regarding Hindustani music can be detected. As result, a more detailed and exact insight into processes of cultural appropriations and transformations in Malay communities can be given. This study discusses essentially Hindustani musical elements used in Malay ghazal performances. This study attempts to investigate the understanding of various Indian musical elements,their application and appropriation within local music practices in Malaysia, mainly in Malay ghazal, by using music transcription and qualitative research methods such as grounded theory, domain analysis, .microanalysis, analytical induction, and discourse analysis. Methodically, this research investigates the process of how elements of Hindustani music culture are applied in Malay ghazal practices. It is to enhance the understanding of some patterns of cultural appropriation and adaptation thus stimulating further discussions. Qualitative musical analyses and historical methods are the main methodological approaches looking into the ghazal transcriptions and current knowledge on the subject matter. The interviews carried out with musicians and other various informants are analysed and subsequently discussed using keywords. The time frame of this study will include essentially the last decades (approx. 1950-2015). However, for examining origin, historical context and evolution of Malay ghazal practices, the time frame must reach back into the late 19th century. This study is significant among many other studies on Malaysian music genres that have not discussed Malay ghazal in historical and musical detail. A central concept explored is the selective tolerance towards musical traces of Hindustani culture. The study shows that Malaysian scholars and musicians have due to diverse reasons limited access to knowledge about Hindustani culture and about Hindustani musical elements used in Malay ghazal. Interestingly, some musical elements of Hindustani culture can be traced in vocal lines as well as in the way musical instruments are played. However, the degree of understanding historical background and meanings given in the culture of departure is not high. Only selected musical elements and performance functions were adapted in Malay ghazal, mainly but not exclusively for ideological and pragmatic reasons. By formulating a detailed account on the evolution and stylistic features of Malay ghazal that state clear traces of Hindustani music within the genre, this study brings new insights and allows for further discussions on patterns of cultural adaptation among Malay communities living in Malaysia.